Essays on banks’ implicit subsidies - Vasconcelos, Lucas Nogueira Cabral de (2024)
This thesis is composed of three articles that explore the implicit subsidies of banks and how they are affected by regulatory, institutional, and political factors and macroeconomic conditions. In the first paper, we investigate the effect of bank resolution reforms on the implicit subsidy of banks across 19 countries. We find that the implementation of bank resolution reforms does not reduce the implicit guarantee of large banks, but it does for the non-large ones. Non-large banks also reduce their risk-taking compared to large banks. Those findings indicate that, while resolution regulations alter the perceived implicit guarantees for non-large banks, they do not impact investors’ perceptions of Too-Big-to-Fail (TBTF) for large banks. In the second paper, we investigate whether extractive institutions affect banks’ funding costs advantage using a cross-country sample of banks from 35 countries. We claim that banks in countries with extractive institutions have the power to impose the use of public resources to guarantee their survival in distressed events, creating implicit subsidies on their funding costs. Our results indicate that the less extractive the institutional environment, the lower the banks' funding advantage. Finally, in the third paper, we explored the effect of fiscal constraints on the value of banks in a cross-country sample. Our results indicate that an increase in fiscal constraints negatively impacts the banks’ valuation, possibly due to the reduction of banks' value composed of implicit or explicit guarantees.